Analytic hierarchy process and technique for order preference by similarity to ideal solution: a bibliometric analysis 'from' past, present and future of AHP and TOPSIS. (9th December 2014) - Mukherjee, Krishnendu
Previous review papers on analytic hierarchy process (AHP) and technique for order preference by similarity to ideal solution (TOPSIS) mainly focused on the application areas and paid scant attention to the framework development of AHP, TOPSIS and their hybrid methods. The purpose of this paper is to review the literature on AHP, type of scale used in AHP, modified AHP, rank reversal problem of AHP, validation of AHP, application of AHP, TOPSIS, normalisation methods for TOPSIS, distance functions for TOPSIS, fuzzy hierarchical TOPSIS, rank reversal problem of TOPSIS and various applications of TOPSIS to prepare a ready-made reference for academician, research scholar and industry people. In this regard, research works are gathered from 1980 to 2013 (searched via Science Direct, IEEE etc.) and out of which 61 research papers are critically assayed to depict the development of AHP, TOPSIS and their hybrid methods. Meaningful information and critical remarks are summarised in various tabular formats and charts to give readers easy information.